2016
DOI: 10.1159/000443510
|View full text |Cite
|
Sign up to set email alerts
|

Er:Yag Laser Treatment of Simple Snorers in an Outpatient Setting

Abstract: Objective: Snoring occurs as a result of soft tissue vibration caused by a partial upper airway collapse during sleep. This study evaluated the effectiveness and potential adverse side effects associated with the use of a nonsurgical, erbium-doped yttrium aluminum garnet (Er:YAG) laser treatment for patients with snoring conditions. Materials and Methods: In total, 33 patients with different degrees of snoring were analyzed retrospectively. All patients received three NightLase™ Er:YAG laser treatments. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…Cetinkaya et al obtained a 65% satisfaction rate in 33 patients after three laser sessions as indicated by the questionnaire. The best results were obtained in the group of patients above 50 years of age [21]. Storchi et al analyzed a group of 40 patients treated for snoring with the Er:YAG laser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetinkaya et al obtained a 65% satisfaction rate in 33 patients after three laser sessions as indicated by the questionnaire. The best results were obtained in the group of patients above 50 years of age [21]. Storchi et al analyzed a group of 40 patients treated for snoring with the Er:YAG laser.…”
Section: Discussionmentioning
confidence: 99%
“…All the above surgical procedures are associated with the need for (local or general) anesthesia and the possibility of complications and pain in the postoperative period. In the recent years, there have been studies on the treatment options of respiratory disorders during sleep using the Erbium: Yttrium Aluminum Garnet (Er:YAG) laser [21][22][23]. This procedure does not require anesthesia and is not associated with pain.…”
Section: Introductionmentioning
confidence: 99%
“…Snoring is a common social problem worldwide, with studies indicating that 45% of people often snore, more often in man and elderly people ( 1 - 3 ). Snoring sound could result from the vibration of the oropharynx tissues when there is a partial collapse of the upper airways, specially of soft palate, lateral walls of the pharynx, and the base of the tongue ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors contribute to this condition such as obesity, alcoholism, consumption of sedatives, smoking, old age, anatomical variations that causes airway obstruction including long soft palate and also uvula with a longer length, hormonal problems, low tonus of the muscles of the throat or tongue, and hypertrophy of tonsils ( 1 - 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation